2010
DOI: 10.5001/omj.2010.11
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Case of Brunneroma Duodenum causing Gastric Outlet Obstraction

Abstract: A case of Brunneroma causing gastric outlet obstruction is presented with radiological, endoscopical findings which was removed laparoscopically.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…Most of the lesions are less than 1 cm in size and asymptomatic. Occasionally, it causes symptoms of obstruction and abdominal pain [6,7]. Endoscopy has a sensitivity of 72-89%, however biopsies may be non-diagnostic as lesions are submucosal and may be missed on pinch biopsy which is one of the possibilities occurred in our case.…”
Section: Discussionmentioning
confidence: 78%
“…Most of the lesions are less than 1 cm in size and asymptomatic. Occasionally, it causes symptoms of obstruction and abdominal pain [6,7]. Endoscopy has a sensitivity of 72-89%, however biopsies may be non-diagnostic as lesions are submucosal and may be missed on pinch biopsy which is one of the possibilities occurred in our case.…”
Section: Discussionmentioning
confidence: 78%
“…Endoscopic polypectomy is a cost effective, less invasive approach that has been shown to be an effective and safe alternative to surgery [14] . In our extensive literature review we found that size and pedunculation were important factors in determining which treatment modality was pursued [15][16][17][18][19][20][21][22][23][24][25][26] . Typically, endoscopic polypectomy was attempted in patients with polyps of less than 5 cm in size and with a pedunculated characteristic [18,20,21,26] .…”
Section: Discussionmentioning
confidence: 99%
“…Typically, endoscopic polypectomy was attempted in patients with polyps of less than 5 cm in size and with a pedunculated characteristic [18,20,21,26] . Surgery was the preferred modality for polyps 5 cm or larger [16,17,[22][23][24] .…”
Section: Discussionmentioning
confidence: 99%
“…Even rare are the large tumours >2 cm size presenting with complications as in this case. Only 2–3 cases have been reported where Brunneroma has been associated with duodenojejunal intussusception 10 11. Acute pancreatitis,12 biliary fistula13 and biliary obstruction may be other presenting features.…”
Section: Discussionmentioning
confidence: 99%